2017
DOI: 10.1101/222398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling microbiome recovery after antibiotics using a stability landscape framework

Abstract: 10Even short courses of antibiotics are known to reduce gut microbiome diversity. However, there has been 11 limited mathematical modelling of the associated dynamical time-response. Here, we take inspiration from a 12 'stability landscape' schematic and develop an impulse-response model of antibiotic perturbation. We fit this 13 model to previously published data where individuals took a ten-day course of antibiotics (clindamycin or 14 ciprofloxacin) and were sampled up to a year afterwards. By fitting an ext… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 50 publications
0
46
0
Order By: Relevance
“…An alternative explanation, however, is that the microbiome is meta-stable, and antibiotic perturbation may transition the structure to an alternative, yet still stable (meta-stable) composition with similar numbers of species and diversity. Indeed, modeling existing datasets of healthy humans treated with antibiotics supports this assertion [56,74,100].…”
Section: Stable Adulthoodmentioning
confidence: 85%
See 1 more Smart Citation
“…An alternative explanation, however, is that the microbiome is meta-stable, and antibiotic perturbation may transition the structure to an alternative, yet still stable (meta-stable) composition with similar numbers of species and diversity. Indeed, modeling existing datasets of healthy humans treated with antibiotics supports this assertion [56,74,100].…”
Section: Stable Adulthoodmentioning
confidence: 85%
“…1) [73]. Indeed, computational modeling of the short-term impact of various antibiotics demonstrates that ciprofloxacin, a broad-spectrum fluoroquinolone antibiotic, showed more displacement from microbiome equilibrium than amoxicillin, a narrow spectrum β-lactam antibiotic [74]. Certain strains of the same species do not recover, suggesting potentially lasting consequences.…”
Section: Stable Adulthoodmentioning
confidence: 99%
“…For example, a single standard course of antibiotics has been shown to alter species composition of the gut and oral microbiomes for over a year. 69,70 Matching of cases and controls is particularly challenging for metagenomics studies given the broad range of microbes considered. 71 Metagenomics studies should aim to minimise and statistically control for host confounders or, at a minimum, list those confounders that might affect interpretation of results.…”
Section: Figure 1: Sources Of Uncertainty Diagram Highlighting Potentmentioning
confidence: 99%
“…Shaw et al . (Shaw et al 2019) reported a simple quantitative model based on a stability landscape framework. They demonstrated that the microbiome existed in multiple stable equilibria of landscape that could be influenced by sufficiently strong perturbations such as antibiotics that could alter the microbiome from its normal equilibrium to other states.…”
Section: Discussionmentioning
confidence: 99%